2021
DOI: 10.3390/ijms221910696
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq and Electrical Penetration Graph Revealed the Role of Grh1-Mediated Activation of Defense Mechanisms towards Green Rice Leafhopper (Nephotettix cincticeps Uhler) Resistance in Rice (Oryza sativa L.)

Abstract: The green rice leafhopper (GRH, Nephotettix cincticeps Uhler) is one of the most important insect pests causing serious damage to rice production and yield loss in East Asia. Prior to performing RNA-Seq analysis, we conducted an electrical penetration graph (EPG) test to investigate the feeding behavior of GRH on Ilpum (recurrent parent, GRH-susceptible cultivar), a near-isogenic line (NIL carrying Grh1) compared to the Grh1 donor parent (Shingwang). Then, we conducted a transcriptome-wide analysis of GRH-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 92 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…The waveforms produced by N. cincticeps feeding were categorized into Nc1-Nc4 (Fig. S3), with Nc1 indicating non-probing, Nc2 indicating stylet penetration into host, Nc3 signifying path and salivation, and Nc4 representing stylet presence in the phloem and xylem tissue 34,35,36,37 . Results showed that knockdown of NcVg expression in leafhoppers significantly prolonged the duration of non-probing (Nc1), and significantly shortened the duration of ingestion from phloem and xylem bundle tissues (Nc4), but had no effect on stylet penetration (Nc2) or salivation (Nc3) (Fig.…”
Section: Salivary Ncvg Functions As An Effector That Suppresses H 2 O...mentioning
confidence: 99%
“…The waveforms produced by N. cincticeps feeding were categorized into Nc1-Nc4 (Fig. S3), with Nc1 indicating non-probing, Nc2 indicating stylet penetration into host, Nc3 signifying path and salivation, and Nc4 representing stylet presence in the phloem and xylem tissue 34,35,36,37 . Results showed that knockdown of NcVg expression in leafhoppers significantly prolonged the duration of non-probing (Nc1), and significantly shortened the duration of ingestion from phloem and xylem bundle tissues (Nc4), but had no effect on stylet penetration (Nc2) or salivation (Nc3) (Fig.…”
Section: Salivary Ncvg Functions As An Effector That Suppresses H 2 O...mentioning
confidence: 99%
“…Given the importance of electrical signals numerous physiological effects of electrical signaling have been described in recent years; 20 . 35–37 …”
Section: Electrical Signalling In Response To Biotic Stressmentioning
confidence: 99%